Bung Sultan : bunga rampai esai tentang lelaku priyayi Jawa / R.P.A. Suryanto Sastroatmodjo ; penyunting, R. Toto Sugiharto. - SURYANTO SASTROATMODJO, R.P.A.; Toto Sugiharto, R. (Adi Wacana, 2008)
xxxiv, 230 hlm. ; 21 cm (3 eks.)